Hubungan Spiritual Well-Being dengan Hardiness pada Pasien Diabetes Melitus Tipe 2 di Poliklinik RS Tingkat III Baladhika Husada Jember - Nurmaidah, Ruri; Widayati, Nur; Sutawardana, Jon Hafan (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Diabetes Mellitus (DM) influence on psychological and physical condition of the patients. Patients arerequired to maintain self-care and to prevent complication which can cause psychological pressure. Thiskind of pressure may affect hardiness of patients in performing self-care. Hardiness may be influenced byspiritual well being. The aim of this study was to analyse the relationship between spiritual well-being andhardiness in patients with type 2 DM. This research applied correlational design with cross-sectionalapproach. A total of 112 respondents were selected by using consecutive sampling technique. The data werecollected by administering questionnaire of Spiritual Well-Being Scale (SWBS) and Hardiness Scale. Dataanalysis was performed by Spearman-rank correlation test with the significance level of 0.05. The resultsshowed that the median score of spiritual well being was 91 (72-100) while the median value of hardinesswas 104 (84-122). There was a significant positive correlation between spiritual well-being and hardiness (pvalue : 0.001 ; r : 0.303). The higher the spiritual well-being the better the hardiness of patients with type 2DM. This research reveals on the importance of assessing spiritual well-being to enhance hardiness inpatients with type 2 DM.